Planejamento experimental aplicando Taguchi em uma soldagem MIG de revestimento 308l - Silva, Marcos Vinícius Tavares da (2019)
Welding coating of carbon steels with stainless steels allows surfaces with specific properties to be obtained from low cost materials. The quality of the coating is determined directly by the proper adjustment of the welding parameters. In this work, the MIG welding process was applied with the current imposition, the base metal was a SAE 1020 carbon steel and the addition metal was a 308L asutenitic stainless steel of 1,00 mm de diametro, with a single weld bead. The statistical method TAGUCHI Ł9"was used in the experimental design and applied the Analysis of Variance of the obtained results. The aim of this work is to optimize the welding parameters (the constant \K", which relates the fusion rate of the electrode to the feed speed of the wire to improve the stability of the electric arc, the distance of the contact nipper piece, the angle of the torch and the speed of welding) in coating welding having as response variables the width, the penetration, the reinforcement, the dilution, the convexity index of the weld bead and the microhardness. The largest width was 11,158 mm, the average reinforcement was 2,8742 mm, the average convexity index was 31,295%. The average values of microhardness were also obtained, being measured in the base metal, in the thermally affected area and in the molten zone and the values obtained indicate the existence of more than one phase present in the material. Current and voltage signals were obtained simultaneously to identify behavioral changes and to determine the stability of the electric arc. Through graphs it was possible to identify that there were no unregular droplet transfer peaks in the current or voltage, and the occurrence of these peaks would indicate the instability of the electric arc, providing poor quality in the weld bead. The results of the experiments, weld bead morphology, microhardness and stress signals, showed that the use of the TAGUCHI method was effective for optimizing the experiments, making it possible to maximize or minimize some response variable of interest.